Seatrout (Salmo trutta) is a natural host for Parvicapsula pseudobranchicola (Myxozoa, Myxosporea), an important pathogen of farmed Atlantic salmon (Salmo salar) - Hansen, Haakon; Poppe, Trygve T; Markussen, Turhan; Karlsbakk, Egil (Parasites & Vectors, 2015)
-